Implicitisation and Parameterisation in Polynomial Functors - Blatter, Andreas; Draisma, Jan; Ventura, Emanuele (Foundations of computational mathematics, 2024)
In earlier work, the second author showed that a closed subset of a polynomial functor can always be defined by finitely many polynomial equations. In follow-up work on GL ∞ -varieties, Bik–Draisma–Eggermont–Snowden showed, among other things, that in characteristic zero every such closed subset is the image of a morphism whose domain is the product of a finite-dimensional affine variety and a polynomial functor. In this paper, we show that both results can be made algorithmic: there exists an algorithm implicitise that takes as input a morphism into a polynomial functor and outputs finitely many equations defining the closure of the image; and an algorithm parameterise that takes as input a finite set of equations defining a closed subset of a polynomial functor and outputs a morphism whose image is that closed subset.